160PClinical outcomes of second-line chemotherapy after progression on nab-paclitaxel plus gemcitabine in patients with metastatic pancreatic adenocarcinoma. (24th November 2019) - Ha, J; Bang, K; Yoo, C; Jeong, J; Chang, H-M; Oh, D; Song, T J; Park, D H; Lee, S S; Lee, S K; Kim, M-H; Park, J-H; et al.
Abstract: Background: Since the introduction of nab-paclitaxel plus gemcitabine (nab-P + GEM) as first-line (1L) treatment for metastatic pancreatic adenocarcinoma (mPDAC), optimal second-line (2L) chemotherapy after progression is unclear. We assessed clinical outcomes of 2L chemotherapy for disease that progressed on 1L nab-P + GEM. Methods: Among the 203 patients previously treated with 1L nab-P + GEM for mPDAC at Asan Medical Center, between February and December 2016, records of 120 patients receiving 2L chemotherapy after progression on nab-P + GEM were retrospectively reviewed. The response rate and survival were evaluated along with analysis of prognostic factors. Results: Fluoropyrimidine-oxaliplatin doublets (FOLFOX or XELOX) were used in 78 patients (65.0%), fluoropyrimidine monotherapy in 37 (30.8%), and liposomal irinotecan plus fluorouracil in 2 (1.7%). The median progression-free survival (PFS) and overall survival (OS) were 3.29 months and 7.33 month from the start of 2L therapy. Fluoropyrimidine-oxaliplatin regimens and fluoropyrimidine monotherapy did not yield significantly different median PFS (2.89 vs 3.81 months, P = 0.40) or OS (7.04 vs 7.43 months, P = 0.86). A high neutrophil-lymphocyte ratio (>2.2) and a short time to progression with 1L nab-P + GEM (<6.4 months) were independent prognostic factors of poor OS with 2L therapy. Conclusions: 2L fluoropyrimidine-oxaliplatin doublets and fluoropyrimidine monotherapy after failure of 1L nab-P + GEM had modest efficacy, with no differences in treatment outcomes between them. Further investigation is warranted for the optimal 2L chemo-regimens and sequencing of systemic chemotherapy for patients with mPDAC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.